Controlled positioning of nanoparticles on a micrometer scale - Enderle, Fabian; Dubbers, Oliver; Plettl, Alfred; Ziemann, Paul (Beilstein Journal of Nanotechnology, 2012)
For many applications it is desirable to have nanoparticles positioned on top of a given substrate well separated from each other and arranged in arrays of a certain geometry. For this purpose, a method is introduced combining the bottom-up self-organization of precursor-loaded micelles providing Au nanoparticles (NPs), with top-down electron-beam lithography. As an example, 13 nm Au NPs are arranged in a square array with interparticle distances >1 µm on top of Si substrates. By using these NPs as masks for a subsequent reactive ion etching, the square pattern is transferred into Si as a corresponding array of nanopillars.
Keywords: electron beam lithography; nanoparticles; positioning; self-assembling; unconventional lithography

(untitled) - Wiedwald, U.; Ziemann, P. (Beilstein J. Nanotechnol., 2010)

(untitled) - Eisenmenger, J.; Schuller, I. K. (Nat. Mater., 2003)

(untitled) - Wiedwald, U.; Han, L.; Biskupek, J.; Kaiser, U.; Ziemann, P. (Beilstein J. Nanotechnol., 2010)

(untitled) - Weller, D.; Moser, A.; Folks, L.; Best, M. E.; Wen, L.; Toney, M. F.; Schwickert, M.; Thiele, J.-U.; Doerner, M. F. (IEEE Trans. Magn., 2000)

(untitled) - Brombacher, C.; Saitner, M.; Pfahler, C.; Plettl, A.; Ziemann, P.; Makarov, D.; Assmann, D.; Siekman, M. H.; Abelmann, L.; Albrecht, M. (Nanotechnology, 2009)

(untitled) - Parkin, S. S. P.; Hayashi, M.; Thomas, L. (Science, 2008)

(untitled) - Spatz, J. P.; Mössmer, S.; Hartmann, C.; Möller, M.; Herzog, T.; Krieger, M.; Boyen, H.-G.; Ziemann, P.; Kabius, B. (Langmuir, 2000)

(untitled) - Bansmann, J.; Kielbassa, S.; Hoster, H.; Weigl, F.; Boyen, H. G.; Wiedwald, U.; Ziemann, P.; Behm, R. J. (Langmuir, 2007)

(untitled) - Bita, I.; Yang, J. K. W.; Jung, Y. S.; Ross, C. A.; Thomas, E. L.; Berggren, K. K. (Science, 2008)

(untitled) - Manzke, A.; Pfahler, C.; Dubbers, O.; Plettl, A.; Ziemann, P.; Crespy, D.; Schreiber, E.; Ziener, U.; Landfester, K. (Adv. Mater., 2007)

(untitled) - Zhang, J.; Li, Y.; Zhang, X.; Yang, B. (Adv. Mater., 2010)

(untitled) - Vogel, N.; Ziener, U.; Manzke, A.; Plettl, A.; Ziemann, P.; Biskupek, J.; Weiss, C. K.; Landfester, K. (Beilstein J. Nanotechnol., 2011)

(untitled) - Meixner, A. J. (Beilstein J. Nanotechnol., 2011)

(untitled) - Gonçalves, M. R.; Makaryan, T.; Enderle, F.; Wiedemann, S.; Plettl, A.; Marti, O.; Ziemann, P. (Beilstein J. Nanotechnol., 2011)

Nanoelectronics and Information Technology - Waser, R. (Wiley-VCH, 2003)

(untitled) - Boyen, H.-G.; Kästle, G.; Weigl, F.; Koslowski, B.; Dietrich, C.; Ziemann, P.; Spatz, J. P.; Riethmüller, S.; Hartmann, C.; Möller, M.; Schmid, G.; Garnier, M. G.; et al. (Science, 2002)

(untitled) - Kinge, S.; Crego-Calama, M.; Reinhoudt, D. N. (ChemPhysChem, 2008)

(untitled) - Goesmann, H.; Feldmann, C. (Angew. Chem., Int. Ed., 2010)

(untitled) - Ziemann, P. (Beilstein J. Nanotechnol., 2011)

(untitled) - Popov, K. I.; Palyulin, V. V.; Möller, M.; Khokhlov, A. R.; Potemkin, I. I. (Beilstein J. Nanotechnol., 2011)

(untitled) - Kästle, G.; Boyen, H.-G.; Weigl, F.; Lengl, G.; Herzog, T.; Ziemann, P.; Riethmüller, S.; Mayer, O.; Hartmann, C.; Spatz, J. P.; Möller, M.; Ozawa, M.; et al. (Adv. Funct. Mater., 2003)

(untitled) - Mena-Osteritz, E.; Urdanpilleta, M.; El-Hosseiny, E.; Koslowski, B.; Ziemann, P.; Bäuerle, P. (Beilstein J. Nanotechnol., 2011)

(untitled) - Auyeung, E.; Cutler, J. I.; Macfarlane, R. J.; Jones, M. R.; Wu, J.; Liu, G.; Zhang, K.; Osberg, K. D.; Mirkin, C. A. (Nat. Nanotechnol., 2012)

(untitled) - Yao, X.; Song, Y.; Jiang, L. (Adv. Mater., 2011)

(untitled) - Aizenberg, J.; Black, A. J.; Whitesides, G. M. (Nature, 1999)

(untitled) - Lee, M. H.; Huntington, M. D.; Zhou, W.; Yang, J.-C.; Odom, T. W. (Nano Lett., 2011)

(untitled) - Walhorn, V.; Paskarbeit, J.; Frey, H. G.; Harder, A.; Anselmetti, D. (Beilstein J. Nanotechnol., 2011)